Di-(2-ethylhexyl) Phthalate Limits the Lipid-Lowering Effects of Simvastatin by Promoting Protein Degradation of Low-Density Lipoprotein Receptor: Role of PPARγ-PCSK9 and LXRα-IDOL Signaling Pathways - Bei-Chia Guo; Ko-Lin Kuo; Jenq-Wen Huang; Chia-Hui Chen; Der-Cherng Tarng; Tzong-Shyuan Lee (MDPI AG, 2023)
Dialysis prevents death from uremia in patients with end-stage renal disease (ESRD). Nevertheless, during hemodialysis, circulating levels of di-(2-ethylhexyl) phthalate (DEHP) are increased due to phthalates leaching from medical tubes. Statins are an effective therapy for reducing the risks associated with cardiovascular diseases in patients with chronic kidney disease; however, the mechanism by which statins fail to reduce cardiovascular events in hemodialysis ESRD patients remains unclear. In this study, we investigated whether DEHP and its metabolites interfere with the lipid-lowering effect of statins in hepatocytes. In Huh7 cells, treatment with DEHP and its metabolites abolished the simvastatin-conferred lipid-lowering effect. Mechanistically, DEHP down-regulated the expression of low-density lipoprotein receptor (LDLR) and led to a decrease in LDL binding, which was mediated by the activation of the PPARγ-PCSK9 and LXRα-IDOL signaling pathways. Additionally, the NOX-ROS-TRPA1 pathway is involved in the DEHP-mediated inhibition of LDLR expression and LDL binding activity. Blockage of this pathway abrogated the DEHP-mediated inhibition in the LDLR expression and LDL binding of simvastatin. Collectively, DEHP induces the activation of the NOX-ROS-TRPA1 pathway, which in turn activates PPARγ-PCSK9- and LXRα-IDOL-dependent signaling, and, ultimately, diminishes the statin-mediated lipid-lowering effect in hepatocytes.